Exploring the motivations and emotions underlying rewarding self-gift giving and how they encourage achievement oriented goals. - Karayiannis, Georgios (2015)
The purpose of this study is to explore consumers’ descriptions of rewarding self-gift behaviour during the entire consumption process, including the motivations and emotions involved and how these encourage towards the achievement of personal oriented goals. The study specifically focuses on luxury self-gifts and attempts to incorporate desires and the cycle of desire with self-gift giving. In doing so, the study adopts an interpretive approach, consistent with the author’s philosophical assumptions, using qualitative interviews to explore the self-gift consumer behaviour for luxury products. The motivations identified and reported include to reward, compensate or motivate towards the attainment of a personal goal. Moreover, other motivations have been identified particularly related to luxury self-gifts, which include motivations to impress others, enhance the individuals’ credibility within the society and communicate or depict status and lifestyles. The emotional states of consumers expressed were predominantly positive, which were also sustained during post consumption, mainly due to the luxury products’ symbolic nature of a personal accomplishment. An emotional attachment was reported for luxury self-gifts that contributed towards motivating individuals to attain personal goals. The study is able to verify that consumers longed for luxury products well in advance, prior to their acquisition as self-gifts. Subsequently, a desired luxury product is perceived similar to a self-gift acquired prior to the attainment of a personal goal, however, is yet to be acquired due to financial barriers that individuals are motivated to overcome by achieving personal goals that would also increase the availability of funds. Any pleasure associated with the realisation of a desired luxury self-gift is mostly maintained, unless the luxury product becomes unfashionable. This study offers further support to previous researchers, which explored and conceptualised the self-gift giving motivations and emotions. Finally, it provides novel insights relating to consumer desires and motivations that should be considered in luxury product self-gift consumer behaviour.